Community mediation in Malaysia: the challenges in practising mediation - Abdul Hak, Nora; Ambaras Khan, Hanna (2015)
Community mediation programme is designed by the Department of National Unity and Integration to provide mediation as a method of dispute resolution at community level. The Department trained “Ahli Jawatankuasa Rukun Tetangga” (Peaceful Neighbourhood Committees) to be the community mediator. The objectives of this paper is study the challenges facing by the community mediators and the Department in practising and providing mediation services to the community, respectively. In writing this paper, qualitative and library based research method were adopted by the authors in gathering data. From the data collected, it is found that mediators are yet to be recognised, there is not much effort to promote community mediation programme, there is lack of information in training provided to the mediators and support from the DNUI for mediators to move forward and the budget for community mediation programme is not much. It is suggested that the community mediation programme in Malaysia to have a proper structure rather than the current loose structure under the Unity Management Department, Department of National Unity and Integration as to ensure that the challenges will be overcome and the programme will be successful and benefited the Malaysians.